MENJEMBATANI RESONANSI DAKWAH DAN PLURALITAS KEISLAMAN: STUDI KASUS PADA CERAMAH MASJID DAN PENGARUHNYA TERHADAP MUSLIM MINORITAS DI DAERAH DAIRI SUMATERA UTARA - Nelly (Jurnal Genta Mulia, 2025)
The activity of preaching by scholars has a key role in their success as preachers as Islamic communicators. This study emerged from the complexity of challenges in spreading preaching and facing the plurality of Islam in the Muslim minority community, especially in the Dairi area, North Sumatra. Preaching to minority Muslims in the Muslim minority community, especially in the Dairi area, North Sumatra, has been going on for a long time. Although there are many objections and obstacles in the journey of preaching, uniquely, even though the Muslim community in Dairi Regency is a minority, the development of preaching and its influence on Muslim citizens is very much felt and quite rapid, it can be seen based on the total number of Muslims who have started to increase over time, then the nuances of Islam are also increasingly crowded with many Islamic activities, big days that are always celebrated by minority Muslims and the personal obedience of Muslim citizens by practicing sharia and starting to avoid actions that are opposed by Islam. This study uses a descriptive qualitative approach with a case study design. This study uses data collection techniques, namely: first, in-depth interviews. Interviews will be conducted involving religious figures, community leaders, and minority Muslims to gain an in-depth view of the dynamics of mosque sermons, the resonance of preaching, and the formation of Islamic identity in the minority Muslim community in the Dairi area, North Sumatra. Second, participatory observation. In this section, researchers are actively involved in mosque activities and community activities to directly understand the interactions and social dynamics in Dairi, North Sumatra. Third, documentation. The documentation referred to here is more about analyzing the text of the sermon to identify themes, narratives, and key messages conveyed. In addition, additional documentation can be in the form of visuals through taking pictures (videos or photos), during the interview and observation process. The results of the study show that although there are challenges, obstacles and difficulties in preaching among minority Muslims, the presence of ustadz who preach at the mosque is very influential and their preaching messages reach the minority Muslim community in Dairi, North Sumatra. Several things that can be seen from the influence of this lecture include the increasing obedience of Muslims in practicing their religious teachings, the lively celebration of Muslim holidays, the increasing number of Muslims and the creation of a life of harmony, peace and high tolerance between religious communities.